Evaluation of Plasma Asymmetric Dimethylarginine Levels and Abdominal Aortic Intima-Media Thickness in Infants of Smoker Mothers - Ozcelik, Huseyin Samet; Arslan, Derya; Deniz, Cigdem Damla; Gunenc, Oguzhan; Vatansev, Husamettin; Uysal, Celil (American Journal of Perinatology, 2020)
Objective Smoking during pregnancy has harmful effects on the fetus and infant. Although some studies suggest that exposure to fetal–maternal smoking adversely affects both fetal growth and cardiovascular development, the mechanisms and biochemical consequences of smoking in pregnancy and newborns are not yet fully understood. We aimed to investigate whether maternal smoking during pregnancy causes fetal cardiovascular effect by measuring serum asymmetric dimethylarginine (ADMA) level and abdominal aortic intima-media thickness (aIMT).Study Design This prospective study was conducted in newborns of smoking mothers and never-smoker control mothers during their pregnancies. The babies were evaluated echocardiographically on the first day following birth. In two-dimensional mode, abdominal aIMT measurements were performed. ADMA was measured in umbilical cord blood at birth.Results There were 25 mothers in the study group and 25 mothers in the control group. Serum ADMA levels were 0.459 ± 0.119 μmol/L in the study group and 0.374 ± 0.1127 μmol/L in the control group (p = 0.034). The aIMT value in the study group was 0.84 ± 0.026 mm and the aIMT value in the control group was 0.63 ± 0.011 mm (p = 0.005).Conclusion We found that both the serum ADMA and the aIMT significantly increased in the group with newborns of smoker mothers compared with the group of the newborns of never-smoker mothers. It may also be suggested that exposure to fetal–maternal smoking adversely affects cardiovascular development.Key Points
Keywords: ADMA; pregnancy; smoking; newborn; abdominal aortic intima-media thickness